70VARIASI KOMPOSISI JERAMI DAN SEKAM PADI TERHADAP MUTU BRIKET BIOARANG - Putra Gunawan; Akhyar Ali; Hanum Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Bio-charcoal briquette is one of the biomass fuel. Biomass used in this research were rice straw and rice husk. The aim of this research was to obtain the best composition of bio-charcoal briquettes using rice straw and rice husk that meet the standard quality of briquette. The research used Completely Randomized Design with five treatments and three replications. The treatments were ratio of rice straw and rice husk 90:10, 75:25, 50:50, 25:75, and 10:90. Data obtained were analyzed using Analysis of Variance and followed by Duncan’s Multiple Range Test at 5% level. The result showed that ratio of rice straw and rice husk in each treatment significantly affected moisture, ash, density, bulk density, calorific value, fuel, and volatile matter. The best treatment was a bio-charcoal briquettes which made from ratio rice straw and rice husk 10:90 with moisture content 9.4543%, ash content 30.2718%, density content 1.0110 g/cm3, crushing strength content 0.0120 kg/cm2, calorific value 3794.3530 cal/g, fuel content 0.0081 g/second, and level of volatile matter 0.0198%.Keywords : Bio-charcoal briquette, rice straw, rice husk